2017
DOI: 10.1177/026119291704500105
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PorcineEx VivoRetina Culture Model for Oxidative Stress Induced by H2O2

Abstract: Oxidative stress is a key player in many ophthalmic diseases. However, the role of oxidative stress in most degenerative processes is not yet known. Therefore, accurate and practical models are required to efficiently screen for therapeutics. Porcine eyes are closely related to the human eye, and can be obtained from the abattoir as a by-product of the food industry. Therefore, they offer excellent opportunities for the development of culture models with which to pre-screen potential therapies, while reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 67 publications
1
62
0
Order By: Relevance
“…39 During research studies on RGCs, ex vivo cultures have been shown to remain viable for 7-10 days, which has facilitated the study of molecular mechanisms involved in disease. [83][84][85][86] A better awareness of the interactions between the retinal pigment epithelium and neural retina could provide a basis for investigating the role of signalling molecules or for testing the effects of potential new therapies. 39,[87][88][89] The adult porcine retina can be used as a suitable model for investigating photoreceptor-specific degeneration processes and enhancing the understanding of the mechanisms playing a role in degenerative neuronal cell death.…”
Section: Rabbitsmentioning
confidence: 99%
“…39 During research studies on RGCs, ex vivo cultures have been shown to remain viable for 7-10 days, which has facilitated the study of molecular mechanisms involved in disease. [83][84][85][86] A better awareness of the interactions between the retinal pigment epithelium and neural retina could provide a basis for investigating the role of signalling molecules or for testing the effects of potential new therapies. 39,[87][88][89] The adult porcine retina can be used as a suitable model for investigating photoreceptor-specific degeneration processes and enhancing the understanding of the mechanisms playing a role in degenerative neuronal cell death.…”
Section: Rabbitsmentioning
confidence: 99%
“…In the last years, we developed retinal organ culture models, to test new therapies without euthanasia of laboratory animals . These models are based on porcine retinae, which can be obtained as a waste product from the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation is regarded as a vital marker for the toxicity induced by oxidative stress. It has been demonstrated that exogenous treatment with hydrogen peroxide increases the levels of LPO, even at low doses the treatments can cause necrosis and apoptosis of brain cells [16,17] suggesting the cellular injury by the action of the free radicals. In our study treatment of brain cultures with hydrogen peroxide resulted in significant high levels of the LPO when compared to the control.…”
Section: Discussionmentioning
confidence: 99%